Long non-coding RNA Malat1 modulates CXCR4 expression to regulate the interaction between induced neural stem cells and microglia following closed head injury - Qin Dong; Pengyu Chen; Wenqiao Qiu; Zhijun Yang; Yanteng Li; Yuhui Zhou; Lili Guo; Dan Zou; Ruxiang Xu; Mou Gao (Stem Cell Research & Therapy)
Abstract Background Closed head injury (CHI) provokes a prominent neuroinflammation that may lead to long-term health consequences. Microglia plays pivotal and complex roles in neuroinflammation-mediated neuronal insult and repair following CHI. We previously reported that induced neural stem cells (iNSCs) can block the effects of CXCL12/CXCR4 signaling on NF-κB activation in activated microglia by CXCR4 overexpression. Here we aim to uncover the mechanism of CXCR4 upregulation in iNSCs. Methods We performed bioinformatic analysis to detect the differentially expressed genes in iNSCs after co-cultured with LPS-activated microglia. Subsequently, we predicted the target genes and performed gain- and loss-of-functional studies, dualluciferase reporter, RNA immunoprecipitation, biotin-coupled miRNA pulldown, fluorescence in situ hybridization and cell transplantation assays to further elucidate the mechanism underlying the immunoregulatory effects of iNSCs. Student’s t-test and one-way analysis of variance (ANOVA) with Tukey’s post hoc test were used to determine statistical significance. Results Our results indicated that Malat1 could act as a sponge of miR-139-5p to modulate the expression of CXCR4 that exerted significant influence on the immunoregulatory effects of iNSCs on the secretion of CXCL12, TNF-α and IGF-1 by activated microglia. Furthermore, Malat1 inhibition blocked the immunoregulatory effects of iNSC grafts on microglial activation as well as neuroinflammation in the injured cortices of CHI mice. Interestingly, NF-κB activation in iNSCs augmented the immunoregulatory effects of iNSCs on microglial activation by activating the axis of Malat1/miR-139-5p/Cxcr4. Notably, we found that TNF-α secreted by activated microglia could bind to TNFR1 at the surface of iNSCs to trigger NF-κB activation in iNSCs. Conclusions In short, our findings reveal a novel role of Malat1 in the immunomodulatory effects of iNSCs on microglial activation, suggesting that transplanted iNSCs may self-perceive the changes of the activated state of microglia and thus make prudential regulation of the neuroinflammation following CHI.